Frameworks, Models, and Methods Applied in Robotic Process Automation: A Systematic Review (2019–2024) - Medina Flores, Jimmy Roberto (2025)
Today, organizations are improving their processes through Robotic Process Automation (RPA), which is a key technology in the digital transformation of companies. This study aims to conduct a systematic literature review from 2019 to 2024 to identify reference frameworks and models for Robotic Process Automation (RPA) projects, analyzing and comparing their characteristics and capabilities to facilitate optimal technology implementation. The study focuses on identifying approaches that maximize organizational benefits and determining scenarios where RPA implementation might not generate substantial value. The research explores and critically compares existing proposals, presenting frameworks and methodologies for the systematic selection and evaluation of tasks suitable for RPA automation. This work contributes to the growing body of knowledge on RPA implementation strategies and provides practical insights for organizations considering adopting this technology.